PEMANFAATAN AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN IPA SEKOLAH DASAR - Gita Prasasti Prihatini Mulyawan; Muhamad Sofian Hadi (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The development of technology today is increasingly rapid, it can be felt in the aspect of Education. Many emerging interactive learning applications that can help the process of learning activities in the world of Education. Augmented Reality (AR) can be defined as a technology that combines two-dimensional or three-dimensional virtual objects into a real environment and then projects them in real time. Cameras with high resolution and the presence of sensors that support the development of Augmented Reality (AR) technology. Learning Media is an intermediary tool between teachers and students as a distributor of messages in order to achieve learning objectives and the creation of an effective and efficient learning process. The use of Augmented Reality (AR) learning media can stimulate the mindset of students so that students can think critically about an existing problem.